"Cleaning with Light": Laser beam surface treatment opens up a wide range of industrial applications thanks to state‐of‐the‐art laser technology. Issue 2 (17th April 2018) - Büchter, Edwin
Abstract: The laser‐based surface pretreatment of industrial components and surfaces is often an economical alternative to conventional component cleaning. In addition to its low energy consumption, the media‐free process does not require any chemicals or abrasives, which is why "cleaning with light" is particularly sustainable and environmentally friendly.